Climate Finance to Address Climate Vulnerability and Increase Resilience: A Review - Gopal, Nikita; Anakha, K. S.; Abhishek, K. H.; Geethalakshmi, V.; De Silva, D. Achini M.; Sajeev, M. V.; Senevirathne, Sulochana; Bandara, Ruwini; Bindu, J. (Fishery Technology, 2026)
This narrative review synthesises insights from 59 peer-reviewed articles, institutional reports, and empirical field studies published primarily between 2010 and 2025, drawn from databases including Google Scholar, ScienceDirect, Scopus, and Web of Science, as well as institutional repositories such as FAO, IPCC, NOAA, and national bodies like the Department of Fisheries, India. It examines the ecological impacts of climate change, emerging adaptation strategies, and the critical role of climate financial services in enhancing sectoral resilience. The review identifies three dominant thematic clusters: vulnerability assessments, adaptation and climate finance initiatives.A central focus of the review is on climate financial services, public, private, and blended financing models, which facilitate investments in climate adaptation and mitigation. International Public finance instruments and public finance instruments at the national level in India and Sri Lanka have been studied separately. Private sector tools offer alternative funding avenues but are constrained by high-risk perceptions and limited project bankability. Blended finance mechanisms, such as the Seychelles Blue Bond and the Global Fund for Coral Reefs, demonstrate the potential to de-risk investments and attract private capital toward sustainable blue economy initiatives.The studies from India and Sri Lanka highlight that concessional credit, parametric insurance, and gender-targeted financial windows can enhance adaptive capacity for small-scale fishers and aquaculture operators. The review underscores that effective fisheries adaptation requires participatory planning, inclusive access to finance, and integration of traditional knowledge with scientific forecasting. These findings provide actionable guidance for policymakers and stakeholders to strengthen sectoral resilience, improve livelihoods, and maintain fisheries productivity under changing environmental conditions.